2003
DOI: 10.1023/a:1023323509888
|View full text |Cite
|
Sign up to set email alerts
|

Generation of CD8+ Cytotoxic T Lymphocytes Against Breast Cancer Cells by Stimulation with Mammaglobin-A-Pulsed Dendritic Cells

Abstract: Mammaglobin-A is exclusively expressed by breast cancer cells. Thus, mammaglobin-A-specific T cell immune responses may be useful for the design of new breast cancer-specific immunotherapies. We show herein that CD8+ T cells generated against recombinant mammaglobin-A-pulsed dendritic cells display a marked cytotoxic activity against mammaglobin-A-positive breast cancer cell lines. This study indicates the immunotherapeutic potential of this novel antigen for the treatment of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Second, mammaglobin is expressed in primary, occult, and metastatic disease, and even though it has not systematically been followed over time during tumor progression, available data suggest that expression is stable. Third, our earlier report [16] and reports from others [24][25][26] show that mammaglobin contains HLA-A2 and HLA-A3-binding peptides that stimulate CD8 T cells in vitro and in vivo in a CD8/HLA-A2 double transgenic mouse model. Thus, mammaglobin may be a suitable target for vaccine therapy of breast cancer.…”
Section: Discussionmentioning
confidence: 74%
“…Second, mammaglobin is expressed in primary, occult, and metastatic disease, and even though it has not systematically been followed over time during tumor progression, available data suggest that expression is stable. Third, our earlier report [16] and reports from others [24][25][26] show that mammaglobin contains HLA-A2 and HLA-A3-binding peptides that stimulate CD8 T cells in vitro and in vivo in a CD8/HLA-A2 double transgenic mouse model. Thus, mammaglobin may be a suitable target for vaccine therapy of breast cancer.…”
Section: Discussionmentioning
confidence: 74%
“…SCGB2A2 expression has been detected, rarely and in low levels, in various normal tissues. This could limit its potential use as an immunotherapeutic target (Manna et al 2003, Viehl et al 2005, due to concerns about autoimmune toxicity. Zafrakas et al (2006a) have recently found an abundant SCGB2A2 expression in malignant and normal tissues of the breast and in the female genital tract, namely the cervix, uterus and ovary, while lower expression levels were rarely found in other tumours and normal tissues (Zafrakas et al 2006a).…”
Section: Scgb2a2mentioning
confidence: 99%
“…More important, adoptive transfer of these MGB-specific CD8 CTL into SCID mice bearing breast cancer xenografts was associated with breast cancer immunity [19]. These and other studies [16,20] have provided evidence that MGB can induce a MGB-specific CD8 T cell response, and that MGB-specific CTL can indeed recognize MGB + breast cancer cells. However, little is known thus far about a possible MGB-induced CD4 T cell response.…”
Section: Introductionmentioning
confidence: 75%
“…MGB is also expressed at comparable levels in non-invasive, invasive and metastatic disease [7], allowing for vaccination at different stages in the course of the disease and as a prevention strategy. We and others have shown that MGB is immunogenic and capable of inducing a CD8 T cell response [15][16][17][18][19][20]. Several human leukocyte antigen (HLA) class I restricted MGB-derived epitopes have been identified, that were recognized by CD8 cytotoxic T lymphocytes (CTL) from breast cancer patients in vitro [15,17,18].…”
Section: Introductionmentioning
confidence: 99%